Toward Unlocking The Full Potential of Acquisitions: The Role of Organizational Restructuring - Barkema, Harry G.; Schijven, Mario (Academy of Management Journal, 2008)
Building on behavioral theory, we study when and how firms unlock synergy from acquisitions over extended periods of time. We argue that initial integration is inevi-tably suboptimal and that, as a result, acquisitive growth decreases an acquirer'sperformance, eventually forcing it to engage in organizational restructuring to more fully unlock the synergistic potential. Hence, we conceptualize organizational restructuring as a second stage in the integration process. Moreover, we theorize about how acquisition-restructuring cycles evolve as firms gain acquisition and restructuring experience. We tested our theory using panel data on firms undertaking almost 1,600 acquisitions over four decades.